THE ISLAMIC BANKING CUSTOMERS’ INTENTION TO USE DIGITAL BANKING SERVICES: AN INDONESIAN STUDY - Harahap, Darwis; Afandi, Ahmad; Siregar, Try Mahendra (Journal of Islamic Monetary Economics and Finance, 2023)
This study examines factors that influence Indonesian Islamic banking customers’ behavioral intention to utilize digital banking services using the Unified Theory of Acceptance and Use of Technology (UTAUT 2). The factors examined include effort and performance expectations, social influence, facilitating conditions, price value, hedonic motivation, habits, trialability, and spiritual motivation. The study also examines whether Islamic lifestyle moderates the roles of social influence, habits, and spiritual motivation in the tendency to utilize Islamic digital banking. Gathering data from 195 Indonesian millennials and utilizing the partial least squares structural equation modeling (PLS-SEM) method, we find that not all factors have a positive effect on the propensity to utilize Islamic digital banking services. The performance expectations, social influences, price values, habits, and Islamic lifestyles all have a strong favorable effect on the desire to use digital banking.  Meanwhile, the facilitating condition, hedonic motivation, trialability, and spiritual motivation only slightly affect the intention to use digital banking. Finally, the paper notes that absence of Islamic lifestyle’s moderating role.